Principal Innovation in Managing Budgetary Autonomy: Evidence from a Narrative Review Using the Saber Framework - Shofiyah, Faridatus; Sumarni, Sri; Saputro, Ardiyan Eko; Puspitasari, Vinda; Prasetyo, Deny (Research, Training and Philanthropy Institution Natural Aceh, 2026)
Vocational education in Indonesia has transformed the implementation of budgetary autonomy in vocational high schools (SMKs), requiring principals to manage resources strategically and accountably. However, most studies emphasise administrative compliance with funding regulations, and few synthesize principals' innovation within the School Autonomy and Accountability (SABER) framework. This study analyses principals' innovation strategies in managing SMK budgetary autonomy via a narrative literature review. Twelve articles (2022–2025) were thematically synthesized. Findings show three dominant innovation patterns: revenue diversification through internal business units such as BLUD and teaching factories; financing efficiency via strategic industry partnerships; and strengthened accountability through digital internal control systems. These innovations suggest that effective budgetary autonomy depends less on funding magnitude and more on principals' entrepreneurial leadership capacity to balance autonomy with strict accountability. The study contributes a conceptual synthesis of SABER in vocational contexts and recommends capacity-building for principals and adaptive regulatory measures to support innovation, particularly in remote and resource-constrained settings, for wider validation.